Reviews Evaluating Information Technology-Based Cardiac Rehabilitation Programs and Support: A Systematic Review - Mahdieh Arian; Ali Valinejadi; Mohsen Soleimani (Iranian Journal of Public Health, 2022)
Background: Application of technology in virtual or remote cardiac rehabilitation programs can resolve the challenge of accessing healthcare services and reduce access level inequalities. This study aimed to evaluate the effect of technology on different clinical outcomes in cardiac rehabilitation programs used for cardiovascular (CVD) patients.